Business model innovation from an open systems perspective: structural challenges and managerial solutions. (1st January 2013) - Berglund, Henrik; Sandström, Christian
There is an emerging consensus that business models are systemic and transcend firm boundaries. Yet, existing research on Business Model Innovation (BMI) challenges focus almost exclusively on intra-firm factors such as capabilities, cognition and leadership. We explore challenges related to BMI by instead drawing on an open systems perspective on organisations. In particular, we argue that the systemic and boundary-spanning nature of business models imply that firms are forced to act under conditions of interdependence and restricted freedom, since they do not have executive control over their surrounding network. Consequently, we propose that suitable managerial solutions include the development of shared knowledge, appropriability regimes based on trust, network stability and the alignment of heterogeneous interests.